2014
DOI: 10.1371/journal.pone.0085538
|View full text |Cite|
|
Sign up to set email alerts
|

Association between CASP8 –652 6N Del Polymorphism (rs3834129) and Colorectal Cancer Risk: Results from a Multi-Centric Study

Abstract: The common −652 6N del variant in the CASP8 promoter (rs3834129) has been described as a putative low-penetrance risk factor for different cancer types. In particular, some studies suggested that the deleted allele (del) was inversely associated with CRC risk while other analyses failed to confirm this. Hence, to better understand the role of this variant in the risk of developing CRC, we performed a multi-centric case-control study. In the study, the variant −652 6N del was genotyped in a total of 6,733 CRC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…There were several reports examining the contribution of caspase-8 rs3834129 in CRC risk in other populations. A multicentric study that included 6,733 CRC cases and 7,576 controls recruited from Spain, Italy, USA, England, Czech Republic and the Netherlands has indicated that rs3834129 was not associated with CRC risk (37). This is consistent with the study conducted by Xiao MS et al which included 305 CRC patients and 342 healthy Chinese controls (38).…”
Section: Discussionsupporting
confidence: 84%
“…There were several reports examining the contribution of caspase-8 rs3834129 in CRC risk in other populations. A multicentric study that included 6,733 CRC cases and 7,576 controls recruited from Spain, Italy, USA, England, Czech Republic and the Netherlands has indicated that rs3834129 was not associated with CRC risk (37). This is consistent with the study conducted by Xiao MS et al which included 305 CRC patients and 342 healthy Chinese controls (38).…”
Section: Discussionsupporting
confidence: 84%
“…As shown in Table 1 , 18 separate studies including a total of 15,086 patients and 16,374 controls were finally retrieved. Among them, there were 3 esophageal cancer studies [12 , 1516] , 3 gastric cancers [12 , 15 , 17] and 12 colorectal cancers (including studies) [15 , 1823] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further biochemical assays illustrated that this variant might lead to decreased apoptotic reactivity of T lymphocytes upon cancer cells stimulation. A multi-centric study conducted by Pardini et al indicated that rs3834129 was not associated with CRC risk in the full data set 21 . This study recruited 6,733 CRC cases and 7,576 controls by six different centers located in Spain, Italy, USA, England, Czech Republic and the Netherlands collaborating to the international consortium COGENT (Colorectal cancer GENeTics).…”
Section: Discussionmentioning
confidence: 97%